Media Sosial Instagram sebagai Pusat Informasi Kota Bandung: (Analisis Isi pada Akun @humas_bandung) - Fikri, Miftahul (Talenta Publisher, 2024)
Currently, social media has become an information center which aims to create awareness among the public to position social media not only as entertainment, but also as a source of information. Social media, which is included in the new media section, is widely used by the public to obtain the information they need. Social media has the advantage of being a digital communication tool that is able to spread messages and events in the form of information to the public, such as Instagram which is chosen and used by the Indonesian people. Instagram users have the opportunity and freedom to absorb information in the city of Bandung. The Instagram account @humas_bandung is one of the accounts that fills in events, happenings and information in the city of Bandung social media with the account @humas_bandung actively uses Instagram to share information and educate the public regarding incidents in the city of Bandung. The purpose of this research is to determine the influence of social media Instagram @humas_bandung on social media as an information center for the city of Bandung. This research uses qualitative content analysis with the direction of finding out uploads from @humas_bandung. The results of this research show that the social media Instagram @humas_bandung is the information center for the city of Bandung.